Horizontal permeability determination from the elliptical flow regime of horizontal wells - Escobar, Freddy Humberto; Muñoz, Oscar Fernando; Sepúlveda, Jairo Antonio (CT&F - Ciencia, Tecnología y Futuro, 2004)
The technological development of the oil industry around the globe has resulted in an increase in drilling horizontal wells due to their great efficiency to produce higher amount of oil per unit pressure drawdown. For this reason, it is fundamental to properly identify, evaluate and model the pressure behavior for this type of wells. The current techniques for interpretation of pressure transient tests in horizontal wells include conventional methods (semilog analysis and Cartesian plot of pressure vs. the square root of time) and semilog and log-log type-curve matching analysis. Defining the accurate starting and ending times of the different flow regimes is a drawback of the conventional technique. Type-curve matching requires all flow regimes to be present. Otherwise, type-curve matching will provide non-unique answers. An additional difficulty in conducting horizontal well interpretation may be due to the absence of some of the flow regimes. A technique to interpret horizontal well pressure data eliminating type-curve matching was introduced in 1996 by Engler and Tiab. In that study, however, the elliptical-flow regime was not included. This flow regime has been recognized as an important aspect in horizontal well testing and some research has been devoted to that issue 2,8. It is characterized by a 0,36-slope line on the pressure derivative log-log plot and its governing equation has been already presented in the literature. In this paper, the elliptical-flow regime is used to develop analytical equations to obtain horizontal permeability anisotropy. The intersection points of the elliptical-flow regime with early-linear, early-radial, late-linear and/or late-linear flow regimes have also been used to find new analytical expressions to verify the horizontal permeability or to find the permeability in the y-direction. The proposed methodology was verified successfully by means of the analysis of two examples reported in the literature.